Gender Violence as a Water, Sanitation, and Hygiene Risk: Uncovering Violence Against Women and Girls as It Pertains to Poor WaSH Access. (December 2018) - Pommells, Morgan; Schuster-Wallace, Corinne; Watt, Susan; Mulawa, Zachariah
The purpose of this study was to better understand the gender violence risks that exist in communities where poor water, sanitation, and hygiene (WaSH) access is a known problem. Focus groups and key informant interviews were used to capture the lived experiences of community and health care practitioners from Rwanda, Tanzania, Uganda, and Kenya. This article provides lived narratives of the various cultural and environmental conditions leading to assaults directly attributable to inadequate WaSH. The results shed light on the complex intersections between water access and violence and have significant implications for achieving gender equity and universal access to WaSH.